1985
DOI: 10.1104/pp.79.1.266
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Changes in Cultured Sorghum Cells in Response to Induced Water Stress

Abstract: ABSTRACITen varieties of Sorghum bicolor (L.) Moench were grown as callus cultures under conditions of water stress, which was induced by addition of polyethylene glycol (molecular weight 8000) in the medium. Growth and free proline were estimated in the control and water-stressed cultures. In all varieties, proline levels were low in the absence of water stress and the levels increased in response to water stress. However, the magnitude of these increases were not correlated with stress tolerance of the indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
1
5

Year Published

1987
1987
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(36 citation statements)
references
References 17 publications
2
28
1
5
Order By: Relevance
“…DISCUSSION Regenerable callus from maize inbred lines B37wx, H99, and Pa9 1 can be induced to tolerate 4C for twice as long as untreated control callus (at least 100 d), with treatments that increase the free proline concentration in the callus (Table I). This observation is similar to other reports in the literature that have linked proline accumulation, in both callus and whole plants, to cold and drought stress tolerance (1,5,8,9,(17)(18)(19)(20)(21)(22). The exact role of proline in the cold tolerance of maize callus is unknown.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…DISCUSSION Regenerable callus from maize inbred lines B37wx, H99, and Pa9 1 can be induced to tolerate 4C for twice as long as untreated control callus (at least 100 d), with treatments that increase the free proline concentration in the callus (Table I). This observation is similar to other reports in the literature that have linked proline accumulation, in both callus and whole plants, to cold and drought stress tolerance (1,5,8,9,(17)(18)(19)(20)(21)(22). The exact role of proline in the cold tolerance of maize callus is unknown.…”
supporting
confidence: 78%
“…Similarly, cultured plant cells have been shown to accumulate proline when placed under salt or osmotic stress (1,8,17,21) and proline has been used to protect a nonregenerable suspension of the maize inbred B73 from exposure to liquid N2 (22).…”
mentioning
confidence: 99%
“…Addition of PEG to the medium produces osmotic stress (Kumar et al 2011) and decreases the water potential (Aazami et al 2010) which negatively effects growth. Decreased growth in the presence of PEG in the medium is reported in sugarcane (Errabii et al 2008) sunflower (Hassan et al 2004) Sorghum (Bhaskaran et al 1985) tomato (Abdel-Raheem et al 2007;Aazami et al 2010). …”
Section: Resultsmentioning
confidence: 94%
“…A similar trend in proline levels is reported in tobacco (Gangaopadhyay 1997) sunflower (Hassan et al 2004). Increase in the proline accumulation on exposing calli to PEG is reported in Sorghum (Bhaskaran et al 1985) rice (Aqeel-Ahmad et al 2007) Proline accumulation under water deficit has been mainly recognized as an osmotic agent (Handa et al 1986). Selected calli exhibited osmotic adjustment in response to PEG stress through the synthesis of solutes like proline.…”
Section: Proline and Protein Accumulationmentioning
confidence: 99%
“…This defense is augmented by increases in the concentrations of various osmoprotectants including proline, sugars, and organic acids (Handa et al, 1983;Steward and Voetberg, 1985;Binzel et al, 1987). Several studies, however, have indicated that proline levels do not necessarily correspond to the tolerance of plants for salt and may be induced only after damage has been sustained (Bhaskaran, Smith, and Newton, 1985;Chandler and Thorpe, 1987;Moftah and Michel, 1987). It may be that some of the heat shock proteins produced by salt stress (Heikkila et al, 1984;Harrington and Aim, 1988) similarly are needed to cope with damaged cellular components.…”
Section: Discussionmentioning
confidence: 99%